Conversion of waste cooking oil to jet biofuel with nickel-based mesoporous zeolite Y catalyst. (December 2015) - Li, Tao; Cheng, Jun; Huang, Rui; Zhou, Junhu; Cen, Kefa
Highlights: Mesoporous zeolite Y was used to convert waste cooking oils to jet biofuel. Mesoporous zeolite Y exhibited high alkane and low aromatic hydrocarbon selectivity. Reaction pathway for transforming waste cooking oil to jet biofuel was proposed. Abstract: Three types of zeolites (Meso-Y, SAPO-34, and HY) loaded with nickel were used to convert waste cooking oil to jet biofuel. Mesoporous zeolite Y exhibited a high jet range alkane selectivity of 53% and a proper jet range aromatic hydrocarbon selectivity of 13.4% in liquid fuel products. Reaction temperature was optimized to produce quality jet biofuel. Zeolite Meso-Y exhibited a high jet range alkane yield of 40.5% and a low jet range aromatic hydrocarbon yield of 11.3% from waste cooking oil at 400 °C. The reaction pathway for converting waste cooking oil to jet biofuel was proposed. Experimental results showed that waste cooking oil mainly deoxygenated to heptadecane (C17 H36 ) and pentadecane (C15 H30 ) through the decarbonylation pathway for the first 3 h. Long chain alkanes cracked into jet range alkanes (C8 –C16 ). Cycloalkanes and aromatic hydrocarbons were produced through cyclization and dehydrogenation pathways.